Exploration of physics concepts with traditional engklek (hopscotch) game: Is it potential in physics ethno-STEM learning? - Rizki, Iqbal Ainur; Suprapto, Nadi; Admoko, Setyo (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2022)
Engklek, is one of the traditional games that have many physics concepts to explore, has the potential to be applied in Ethno-STEM-based physics learning. So far, no study has been carried out on exploring the physical concept of this game. Hence, this study aims to explore the concepts of physics in traditional Engklek game and its potential applications in Ethno-STEM-based physics learning. This study uses a qualitative research method with an exploratory design. Data collection using three methods: observations, interviews, and literature studies.Data were analyzed descriptively through three stages: data reduction, presentation, and verification or inference. The results show that the main physics concepts contained in this game are parabolic motion; work and energy; momentum and impulse; and equilibrium of rigid body. This game also can be applied to physics learning because it is relevant to the 2013 curriculum and the Ethno-STEM review. Therefore, the Engklek game can be more meaningful, fun, interactive, and contextual physics learning media. This research implies that the results of exploration and analysis of its potential application to Ethno-STEM-based science learning can be tested for future research or applied directly to physics learning. It is hoped that this learning can increase students' learning motivation while preserving the local wisdom game of Engklek